Playing dirty : sexuality and waste in early modern comedy - Stockton, Will (University of Minnesota Press, 2011)
Playing Dirty is full of dirty jokes. Arguing that the early modern excremental body is in many ways an erotic body, Will Stockton with humor and dry wit reads psychoanalytic theory through early modern comedies, claiming that it is helpful, rather than inimical, to the project of historicizing the body. Noting that psychoanalysis has traditionally operated in a paranoid framework that relentlessly produces evidence of the same ôtruths, ö Stockton turns to a minority practice in psychoanalysisùassociated with Jean Laplancheùto develop a more ôplayfulö analytic for literary studies. This analytic.